A note on carbon taxes and trade spillovers within Europe - Chakraborty, Saptorshee Kanto; D'Amato, Alessio; Mazzanti, Massimiliano (Frontiers in Environmental Economics, 2023)
Carbon taxation is a highly debated environmental policy tool and can contribute to tackling climate change. Before the advent of the emission trading system in the European Union, forms of carbon taxation were present in some EU member states; furthermore, after the approval of the well-known EU Green Deal, carbon taxes can gain momentum in addressing emissions from sectors not involved in the EU Emissions Trading System. Due to this historical evolution of environmental policies over the last decades and in the presence of a system that assigns to EU member states, the governance of energy and fiscal issues, heterogeneous carbon/energy policy settings may determine the impact on growth and trade. This article provides food for thought for a policy through an empirical evaluation of the impact on the gross domestic product of trade spillovers related to carbon taxation in the European Union.